1992
DOI: 10.1093/geront/32.5.656
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving: Role Engulfment and the Loss of Self

Abstract: "Loss of self" was examined in a sample of spouses and adult children caring for a relative with Alzheimer's disease. Defined as a loss of identity that comes about as a result of engulfment in the caregiver role, it was found to be more common among spouses, females, and younger caregivers. Limited social contact and lack of social roles outside that of caregiver were found to be related to greater loss of self. It is associated with lower self-esteem and mastery and with greater depressive symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
168
0
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(181 citation statements)
references
References 0 publications
10
168
0
3
Order By: Relevance
“…3(a), shows that the scenario's almost have a similar pattern, but 3(a) has a substantial decrease in a caregiver's long term stress level after the first half of the simulation. It is consistent with the findings that caregivers with a positive personality, empathic, and high personal resources tend to help more if they experienced less negative event [3], [8]. Meanwhile, Fig.…”
Section: Results #supporting
confidence: 90%
See 1 more Smart Citation
“…3(a), shows that the scenario's almost have a similar pattern, but 3(a) has a substantial decrease in a caregiver's long term stress level after the first half of the simulation. It is consistent with the findings that caregivers with a positive personality, empathic, and high personal resources tend to help more if they experienced less negative event [3], [8]. Meanwhile, Fig.…”
Section: Results #supporting
confidence: 90%
“…Another important concept that can derived from these coping strategies is the relationship focused coping (positive or negative). The combination of high caregiver's empathy (perceiving the inner feeling of care recipient) and problem-focused coping will lead to positive relationship coping, and vice versa [4], [7], [8]. The third aspect is related to the caregiver's outcome.…”
Section: Underlying Principles In Informal Caregiving Interactionsmentioning
confidence: 99%
“…As has been suggested by various authors (Skaff and Pearlin, 1992;Montgomery and Koloski, 1994;Roig et al, 1998) the observed differences between spouse and adult-child caregivers could be related to the different nature of the relationship involved. In the case of spouses, caregiving tasks would be regarded as part and parcel of the marital commitment, whereas for adult-child caregivers such tasks may be felt to have an important and disruptive effect on their lifestyle.…”
Section: Overall Burden and Differences Between Spouses And Adult Chimentioning
confidence: 68%
“…Tarrier and colleagues (2004), for instance, have found that suicidal ideation among persons with psychosis was linked to hopelessness, which was in turn linked to negative self-evaluation. Speaking to the long-term effects of stigma, several authors have suggested that beyond having an immediately distressing impact, stigma may be internalized (Ritsher and Phelan, 2004), and impede a person's chances of establishing identities unrelated to mental illness (Corrigan and Watson, 2002;Skaff and Pearlin, 1992) paving the way to even more entrenched forms of psychosocial dysfunction (McCay and Seeman, 1998).…”
Section: Introductionmentioning
confidence: 99%